1970
DOI: 10.3329/jbcps.v24i2.149
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology in the Guillain-Barré Syndrome: Study of 30 Cases

Abstract: Thirty consecutive patients diagnosed clinically as Guillain Barré Syndrome (GBS) were enrolled in this study to see the electrophysiological patterns of GBS in Bangladeshi community. Among 30 patients, 25 were male (M: F = 5:1) and 47% patients were between 16 and 25 years of age. An antecedent event was present in 67% of patients. An elevated protein was present in 90% of cases and a cell count of up to five was present in 94% of patients. Acute inflammatory demyelinating polyradiculopathy (AIDP) was commone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…This is almost consistent with the study of Kundu 23 where he observed AIDP 33.3%, AMSAN 26.66%, AMAN and AIDP 26.66% and AMAN 13.33%. But another study in Bangladesh showed that electrophysiologically 67% patients had axonal variant of GBS.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is almost consistent with the study of Kundu 23 where he observed AIDP 33.3%, AMSAN 26.66%, AMAN and AIDP 26.66% and AMAN 13.33%. But another study in Bangladesh showed that electrophysiologically 67% patients had axonal variant of GBS.…”
Section: Discussionsupporting
confidence: 80%
“…White blood cell count was below 5/mm 3 in all patients. Similar findings were found by Kundu 23 who observed in his study that cerebrospinal fluid protein was elevated in 90.0% patients and in 93.3% cases cerebrospinal fluid total cell count was up to 5 cells/mm 3 and in only 6.7% patients total cell count was up to 15 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, mean age of patients is lower in AMAN (2nd decades) and AMSAN (3rd decades) than AIDP in this study. [11][12][13][14] About twothirds patients (62.86%) presented with both upper and lower limbs weakness whereas one-third (31.43%) complained of facial weakness and 13.2% has bulbar paralysis. Antecedent events are present in two thirds of the patients (66%) in preceding weeks (one to four weeks).…”
Section: Discussionmentioning
confidence: 99%